2020
DOI: 10.1080/14616696.2020.1719179
|View full text |Cite
|
Sign up to set email alerts
|

Child’s age at parental death and university education

Abstract: Losing a parent due to premature death is generally associated with negative child outcomes. However, the study of possible (modifying) effects of the child's age and family background has been neglected in previous research. In this paper, we analyse the relationship between the child's age at parental death and the child's university education, and we study whether the possible association is modified by the child's family background. We apply ordinary least square regression and linear sibling fixed effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Another related study, by Kalil et al (2016), found that the marginal effect of losing a father was greater at higher levels of paternal education. Although we use a different specification, our findings are similar to Kailaheimo-Lönnqvist and Erola (2020), who found that either parental SES does not play any moderating role following parental death, or that losing a higher SES parent has an equalizing effect on offspring attainment, based on our analyses of extended kin.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Another related study, by Kalil et al (2016), found that the marginal effect of losing a father was greater at higher levels of paternal education. Although we use a different specification, our findings are similar to Kailaheimo-Lönnqvist and Erola (2020), who found that either parental SES does not play any moderating role following parental death, or that losing a higher SES parent has an equalizing effect on offspring attainment, based on our analyses of extended kin.…”
Section: Discussionsupporting
confidence: 85%
“…Biblarz and Raftery, 1993;McLanahan and Sandefur, 1994;Martin, 2012;Bernardi and Radl, 2014;Erola and Jalovaara, 2017). The most comparable studies to our own examined register data in order to measure SES differentials in the loss and compensation processes surrounding parental death in Finland (Prix and Erola, 2017, Kailaheimo-Lönnqvist andErola, 2020). Prix and found that high levels of education amongst mothers did successfully compensate for the death of the father for educational transitions to upper-secondary education and tertiary vocational education, but not for the transition to university education.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations